Analyzing intercultural competence among Erasmus students - Silva, Goretti; Oliveira, Mariana; Correia, Alexandra; Brito, Maria José (Journal of International Students, 2026)
This study examines intercultural competence among students participating in an Erasmus mobility program at higher education institutions across Europe (primarily Portugal, Spain, and Finland). The study adopts a quantitative approach based on an intercultural competence scale. It explores how intercultural competence varies according to both personal characteristics (gender, nationality, field of study, and travel frequency) and students’ perceptions of their attitudes across multiple domains via Mann‒Whitney and Kruskal‒Wallis tests. Moreover, the study seeks to examine correlations between intercultural competence and integration experiences, as well as between intercultural competence and the impact of the Erasmus program on the host community, using Spearman’s tests. Statistically significant differences across groups and correlations between variables are identified whenever they exist. The findings are particularly valuable for educators, policymakers, and tourism professionals when designing programs and initiatives to foster intercultural learning and exchange.